PEMANFAATAN PELAKSANAAN LOKAKARYA MINI PUSKESMAS OLEH PETUGAS PENANGGUNGJAWAB PROGRAM DALAM RANGKA PENCAPAIAN TARGET KINERJA PROGRAM UKM (UPAYA KESEHATAN MASYARAKAT) ESENSIAL DI PUSKESMAS AEK HABIL KOTA SIBOLGA TAHUN 2019 - Hutagalung, Nurdiawani (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2021)
One of the duties of the Puskesmas is to carry out Community Health Efforts with indicators that assess the achievement of the Minimum Service Standards target. Achievement of Minimum Service Standards indicates that there are essential Public Health Effort programs that have not reached the target. The forum used to help achieve the Minimum Service Standard targets is a mini Puskesmas workshop. This study aims to determine the use of the mini Puskesmas workshop by the program officer in achieving the performance targets of the Essential Public Health Efforts program at the Puskesmas. The research method uses descriptive exploratory qualitative. The main informant is the person in charge of the essential Public Health Program and the additional informant is the Head of the Puskesmas, the Coordinator of Public Health Efforts and the financial manager. The results showed that the knowledge of program managers about the mini workshop was quite good, they considered the mini workshop very important and carried out the resulting agreement. But the mini workshop did not guarantee that the performance target would be achieved. Many factors hindered it, on Maternal and Child Health because the K4 achievement calculation could not be completed in one year and K4 drop out. In the family planning program, mothers of childbearing age are reluctant to use contraceptives and their husband's perception is not good. In the Disease Prevention and Control program on early detection of cervical and breast cancer, the reluctance of women aged 30-50 years to do early detection is due to shame, lack of knowledge, perceptions of poor health, and the lack of active roles from cadres and cross-sectoral. In screening visual and hearing acuity due to new performance indicators, lack of competence and number of officers. It is recommended that the person in charge of the program be more active in managing the program, coordinating with other programs and for the Head of the Puskesmas to improve monitoring and evaluation of the performance of the person in charge of the program.